Evaluation of Installation Quality on Polyethelene Pipe Performance under Surcharge Loads - Terzi, Niyazi U.; Dusunceli, Necmi; Yilmazturk, Ferruh; Yildirim, S. (AMER INST PHYSICS, 2010)
In this study, a comprehensive laboratory test on 100 mm diameter HDPE 100 polyethylene flexible pipe buried in quartz sand is described. The laboratory test was performed in a 40 mm thick plexiglass-fronted test tank which replicated a classical trench section in field conditions. The polyethylene flexible pipe was positioned against the glass with its longitudinal axis perpendicular to the glass. This allowed direct observation of the backfill-pipe interactions and pipe performance under surcharge loads. Three high definition photogrammetric cameras were taken photogrammetric images through the glass allowing the discrete measurement and image processing of the deformation patterns of the polyethelene pipe conduit during the pipe installation and incremental surcharge loading. Vertical loads were applied in increments of 10 kPa to 150 kPa using air pressure membranes. According to the test results, it is understood that the installation technique and backfill properties have an important effect on circumferential strains, performance and deformation characteristics of polyethelene HDPE pipe. It was also observed that close-range image processing is a very simple and appropriate method for measuring three dimensional pipe deformations under various conditions.
Keywords: HDPE flexible pipe; Soil-Pipe Interaction; Physics; Polymer Science